Environmental Summits and Innovation - Daryna Grechyna; Pamela Efua Ofori (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This study examines the impact of Conference of the Parties (COP) summits on innovation using an event study framework. Innovation is measured by patent grants, distinguishing between the total number of patents and the number of patents in environmental technologies, based on the World Intellectual Property Organization classification. We find that hosting a COP summit leads to a significant and lasting increase in the total number of patent grants, with an average rise of about 35 percent per year from the seventh to the thirteenth year after the summit, but has only a limited effect on the number of patent grants in environmental technologies. We further examine potential heterogeneity in the effects of COP summits by analyzing the impact of hosting a summit on patents in environmental technology compared to other technologies separately for each host country. The results suggest that while hosting a COP summit generally promotes environmental patenting, the effect is negative in some countries. We discuss possible reasons, including diminishing returns in green innovation and the influence of large industrial emitters. The findings are robust across alternative estimators, the inclusion of control variables, and different measures of patenting activity.
Keywords: O34; O44; Q54; 330; COP summits; environmental technologies; patents; innovation; event study